Important Mathematical formulas

Important Mathematical formulas::

1. (α+в)²= α²+2αв+в²
2. (α+в)²= (α-в)²+4αв
3. (α-в)²= α²-2αв+в²
4. (α-в)²= (α+в)²-4αв
5. α² + в²= (α+в)² – 2αв.
6. α² + в²= (α-в)² + 2αв.
7. α²-в² =(α + в)(α – в)
8. 2(α² + в²) = (α+ в)² + (α – в)²
9. 4αв = (α + в)² -(α-в)²
10. αв ={(α+в)/2}²-{(α-в)/2}²
11. (α + в + ¢)² = α² + в² + ¢² + 2(αв + в¢ + ¢α)
12. (α + в)³ = α³ + 3α²в + 3αв² + в³
13. (α + в)³ = α³ + в³ + 3αв(α + в)
14. (α-в)³=α³-3α²в+3αв²-в³
15. α³ + в³ = (α + в) (α² -αв + в²)
16. α³ + в³ = (α+ в)³ -3αв(α+ в)
17. α³ -в³ = (α -в) (α² + αв + в²)
18. α³ -в³ = (α-в)³ + 3αв(α-в)
ѕιη0° =0
ѕιη30° = 1/2
ѕιη45° = 1/√2
ѕιη60° = √3/2
ѕιη90° = 1
¢σѕ ιѕ σρρσѕιтє σƒ ѕιη
тαη0° = 0
тαη30° = 1/√3
тαη45° = 1
тαη60° = √3
тαη90° = ∞
¢σт ιѕ σρρσѕιтє σƒ тαη
ѕє¢0° = 1
ѕє¢30° = 2/√3
ѕє¢45° = √2
ѕє¢60° = 2
ѕє¢90° = ∞
¢σѕє¢ ιѕ σρρσѕιтє σƒ ѕє¢
2ѕιηα¢σѕв=ѕιη(α+в)+ѕιη(α-в)
2¢σѕαѕιηв=ѕιη(α+в)-ѕιη(α-в)
2¢σѕα¢σѕв=¢σѕ(α+в)+¢σѕ(α-в)
2ѕιηαѕιηв=¢σѕ(α-в)-¢σѕ(α+в)
ѕιη(α+в)=ѕιηα ¢σѕв+ ¢σѕα ѕιηв.
 ¢σѕ(α+в)=¢σѕα ¢σѕв – ѕιηα ѕιηв.
 ѕιη(α-в)=ѕιηα¢σѕв-¢σѕαѕιηв.
 ¢σѕ(α-в)=¢σѕα¢σѕв+ѕιηαѕιηв.
 тαη(α+в)= (тαηα + тαηв)/ (1−тαηαтαηв)
 тαη(α−в)= (тαηα − тαηв) / (1+ тαηαтαηв)
 ¢σт(α+в)= (¢σтα¢σтв −1) / (¢σтα + ¢σтв)
 ¢σт(α−в)= (¢σтα¢σтв + 1) / (¢σтв− ¢σтα)
 ѕιη(α+в)=ѕιηα ¢σѕв+ ¢σѕα ѕιηв.
 ¢σѕ(α+в)=¢σѕα ¢σѕв +ѕιηα ѕιηв.
 ѕιη(α-в)=ѕιηα¢σѕв-¢σѕαѕιηв.
 ¢σѕ(α-в)=¢σѕα¢σѕв+ѕιηαѕιηв.
 тαη(α+в)= (тαηα + тαηв)/ (1−тαηαтαηв)
 тαη(α−в)= (тαηα − тαηв) / (1+ тαηαтαηв)
 ¢σт(α+в)= (¢σтα¢σтв −1) / (¢σтα + ¢σтв)
 ¢σт(α−в)= (¢σтα¢σтв + 1) / (¢σтв− ¢σтα)
α/ѕιηα = в/ѕιηв = ¢/ѕιη¢ = 2я
 α = в ¢σѕ¢ + ¢ ¢σѕв
 в = α ¢σѕ¢ + ¢ ¢σѕα
 ¢ = α ¢σѕв + в ¢σѕα
 ¢σѕα = (в² + ¢²− α²) / 2в¢
 ¢σѕв = (¢² + α²− в²) / 2¢α
 ¢σѕ¢ = (α² + в²− ¢²) / 2¢α
 Δ = αв¢/4я
 ѕιηΘ = 0 тнєη,Θ = ηΠ
 ѕιηΘ = 1 тнєη,Θ = (4η + 1)Π/2
 ѕιηΘ =−1 тнєη,Θ = (4η− 1)Π/2
 ѕιηΘ = ѕιηα тнєη,Θ = ηΠ (−1)^ηα
1. ѕιη2α = 2ѕιηα¢σѕα
2. ¢σѕ2α = ¢σѕ²α − ѕιη²α
3. ¢σѕ2α = 2¢σѕ²α − 1
4. ¢σѕ2α = 1 − ѕιη²α
5. 2ѕιη²α = 1 − ¢σѕ2α
6. 1 + ѕιη2α = (ѕιηα + ¢σѕα)²
7. 1 − ѕιη2α = (ѕιηα − ¢σѕα)²
8. тαη2α = 2тαηα / (1 − тαη²α)
9. ѕιη2α = 2тαηα / (1 + тαη²α)
10. ¢σѕ2α = (1 − тαη²α) / (1 + тαη²α)
11. 4ѕιη³α = 3ѕιηα − ѕιη3α
12. 4¢σѕ³α = 3¢σѕα + ¢σѕ3α
 ѕιη²Θ+¢σѕ²Θ=1
 ѕє¢²Θ-тαη²Θ=1
 ¢σѕє¢²Θ-¢σт²Θ=1
 ѕιηΘ=1/¢σѕє¢Θ
 ¢σѕє¢Θ=1/ѕιηΘ
 ¢σѕΘ=1/ѕє¢Θ
 ѕє¢Θ=1/¢σѕΘ
 тαηΘ=1/¢σтΘ
 ¢σтΘ=1/тαηΘ
 тαηΘ=ѕιηΘ/¢σѕΘ

Leave a Reply

Your email address will not be published. Required fields are marked *